Integration of Pragmatic Aspects in Buying and Selling Transactions During The Implementation of The Sunday Festival in Lhokseumawe City - Rahayu, Ririn; Iqbal, Muhammad; Azhari, Azhari; Ahyar, Juni; Jannah, Miftahul; Bancin, Nurhasanah (Journal of Comprehensive Science, 2024)
This research aims to explain locutionary, illocutionary and perlocutionary speech acts in buying and selling transactions during the Ahad Festival in Lhokseumawe City. This study focuses on the identification and classification of locutionary, illocutionary and perlocutionary speech acts used by traders and buyers in the buying and selling interaction process. This research uses qualitative research, with data collection techniques in the form of recording techniques, listening techniques and note-taking techniques. The data in this research are in the form of sellers' and buyers' statements when buying and selling transactions are taking place, while the data sources in this research are sellers and buyers at the Sunday Festival in Lhokseumawe City. The results of the research show that the data obtained by the researcher was 47 data with a classification of 11 data of locutionary speech acts, 23 data of illocutionary speech acts and 5 data of perlocutionary speech acts.